My Windows 10 - Murray, Katherine, 1961- (Que, 2018)
My Microsoft® Windows® 10 is an easy, full-color tutorial on the latest operating system from Microsoft. This new edition covers the Fall Creators Update to Windows 10. This book is also part of Que's Content Update Program. As Microsoft updates features of Windows 10, sections of this book will be updated or new sections will be added to match the updates to the software. The updates will be delivered to you via a FREE Web Edition of this book, which can be accessed with any Internet connection. To learn more, visit informit.com/CUP . Step-by-step instructions with callouts to Windows 10 photos that show you exactly what to do. Help when you run into Windows 10 problems or limitations. Tips and Notes to help you get the most from your Windows 10 computer. Full-color, step-by-step tasks walk you through getting and keeping your Windows 10 computer working just the way you want. Learn how to · Get creative with innovative new features in Windows 10 Fall Creators Update · Create photo albums and video projects on the fly using your favorite pictures and songs · Use the new My People Hub to keep in touch with friends and family · Ask Cortana to help you find information, schedule appointments, create tasks, and more · Read ebooks or listen to audiobooks in the updated Microsoft Edge browser · Discover, download, and rate apps and ebooks from the Windows Store · Copy, move, and share files and folders using File Explorer · Use the Skype app to message your contacts and make easy--and free--audio and video calls · Make the most of new and enhanced gaming features using the Game bar and live game streaming · Create in three dimensions using Paint 3D and Remix 3D · Use OneDrive to access your files everywhere, on any device you choose · Make your computer more secure than ever, thanks to Windows Defender Advanced Threat Protection.